Agricultural Policy, Program Underperformance, and Food Security in Azerbaijan: Structural Constraints in a Post-Oil Economy - Gubad Ibadoghlu (ZBW - Leibniz Information Centre for Economics, 2025)
This article examines the structural challenges facing Azerbaijan's agrarian sector and their implications for food security in the context of a hydrocarbon-dependent, post-oil economy. Drawing on official statistics from the State Statistical Committee and program documents from the Ministry of Agriculture, the study evaluates the outcomes of major state programs in cotton, tobacco, rice, tea, sericulture, viticulture, and sugar beet production over the period 2012–2024. The analysis reveals substantial underperformance relative to planned targets, with implementation rates for key programs ranging from only 3.9 percent in sericulture to 61.4 percent in cotton. These shortfalls reflect persistent weaknesses in planning, inter-agency coordination, monitoring and evaluation, and private-sector participation. Complementing the program assessment, the article analyzes food self-sufficiency ratios for 2020–2024 across livestock, crop, and processed food categories. The findings demonstrate a dual structure: while Azerbaijan achieves high and often surplus production in horticultural and export-oriented commodities (e.g., vegetables, fruits, nuts, and pomegranates), self-sufficiency in strategic staples such as wheat, grains, rice, and vegetable oils remains low and volatile. Livestock and processed food segments exhibit moderate but stagnant self-sufficiency, constrained by technological gaps, import-dependent inputs, and limited value-chain integration. Overall, the evidence indicates that state-led expansion strategies have not translated into broad based productivity gains, robust food security, or resilient rural development. The article concludes that a shift from politically driven, target-based interventions toward a coherent, market-oriented, and evidence-based policy framework is essential if agriculture is to become a dynamic driver of non-oil diversification and long-term food security in Azerbaijan.
Keywords: Q13; 330; Azerbaijan; Agriculture; State Programs; Food Self-Sufficiency; Structural Reform; Import Dependence; Non-Oil Diversification; Rural Development; Agro-Food Value Chains